Swarm intelligence in data classification - Mohd. Afizi Mohd. Shukran; Mohd Sidek Fadzil Mohd Yunus; Muhammad Naim Abdullah
Data classification involves solving problems by analysing data already present in databases. Due to the explosive growth of both business and scientific databases, extracting efficient classification rules from such databases has become an important task. This is because classificationtechnique is an important form of knowledge extraction and can help to make key decisions.Nevertheless, classification technique can be improved by integrating the latest technology, namely, swarm intelligence.